Studies on the evaluation of surface coating based on epoxy resins in improving the corrosion resistance of steel in concrete - Selvaraj, R.; Bhuvaneshwari, B. (Journal of Structural Engineering, 2025)
The performance of rebar surface coatings based on epoxy - silicone-polyamide resin combination has been evaluated using different mechanical tests and accelerated tests such as salt spray test, electrochemical impedance spectroscopy, impressed voltage test, chemical resistance test, anodic polarisation study and finally by field exposure studies. It is found that two out of four coatings formulations perform well as durable and very effective surface coatings under all environmental conditions.This study also brings out the fact that coatings on steel substrate prepared by chemical cleaning perform as effective as that prepared by mechanical method.